1999
DOI: 10.1136/gut.45.6.895
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin 10 and interleukin 11 in patients with acute pancreatitis

Abstract: Background-Proinflammatory and antiinflammatory cytokines are involved in the pathogenesis of acute pancreatitis. Aims-To measure the serial serum levels of interleukin 10 and interleukin 11 in patients with acute pancreatitis and analyse the relation of these antiinflammatory cytokines to disease severity. Methods-In 50 patients with acute pancreatitis, the serum concentrations of interleukin 10 and interleukin 11 were determined on days one, two, three, four, and seven after admission. Serum C reactive prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 33 publications
2
42
2
2
Order By: Relevance
“…Though 1 study reported sensitivity of 67% and specificity of 100% with IL-10 for prediction of severity on first day of AP, [24] other studies have stated less reliable results compared with IL-6 and IL-8. [19] Tumor necrosis factor alpha (TNF-α), which is produced primarily by macrophages, is a cytokine that stimulates acute phase reaction.…”
Section: Discussionmentioning
confidence: 92%
“…Though 1 study reported sensitivity of 67% and specificity of 100% with IL-10 for prediction of severity on first day of AP, [24] other studies have stated less reliable results compared with IL-6 and IL-8. [19] Tumor necrosis factor alpha (TNF-α), which is produced primarily by macrophages, is a cytokine that stimulates acute phase reaction.…”
Section: Discussionmentioning
confidence: 92%
“…The elevated IL-6 levels in AP may serve as markers of severity of pancreatitis (Galloway and Kingsnorth, 1994), as well as being associated with the occurrence of remote organ complications (Suzuki et al, 2000). Plasma IL-10 levels have been reported to correlate with the severity of pancreatitis and could also be used as an indicator of severity (Chen et al, 1999). The magnitude of the anti-inflammatory response in patients with AP have been demonstrated to predict the clinical outcome (Mentula et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This results in an imbalance between pro-and anti-inflammatory cytokines, resulting in the development of SIRS. Some mediators, such as TNF-alpha, phospholipase, and kinin, are increased greatly in animal models of SAP [9] , and some studies have shown that there is a significant correlation between the serum levels of IL-1-beta, IL-6, IL-8, IL-10 and IL-11 and the severity of acute pancreatitis [24][25][26][27] . Animal studies have shown that early blockade of the cytokine cascade at the level of the IL-1 receptor significantly decreases the severity of pancreatitis and intrinsic pancreatic damage, as well as the mortality from SAP [28,29] .…”
Section: Discussionmentioning
confidence: 99%